New species of Euplocania Enderlein (Psocodea, ‘Psocoptera’, Ptiloneuridae) from Brazil, with a checklist of all known species of the genus - Da Silva Neto, Alberto Moreira; Aldrete, Alfonso N. García; Rafael, José Albertino (Zootaxa, 2019)
Seven new species of Brazilian Euplocania are described and illustrated, five species belong in the amabilis species group (Euplocania bujariensis n. sp., Euplocania cearaensis n. sp., Euplocania hutchingsi n. sp., Euplocania pseudopictaoides n. sp. and Euplocania xavieri n. sp.) one species belong in the marginata species group (Euplocania uariniensis n. sp.) and one species is not assignable to any of the known species groups of the genus. For this species, E. quinquedivisa n. sp., a new species group is here diagnosed, the quinquedivisa group. Information on sexes known and distribution is included for all known species of Euplocania. The first identification key to males of Euplocania species from Brazil is presented.